(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2016)
We describe the treatment of a young girl age, 24 years, with class II division 1 malocclusion and spacing of upper anterior segment. Treatment consisted mainly of space closing, arch contraction, leveling and alignment with Edgewise fixed appliances by multiloop technique. Due to patient good cooperation, treatment time reduced (10 months). The treatment resulted in proper alignment of upper & lower anterior segment, an ideal overjet, overbite and incisor angulations. Ban J Orthod & Dentofac Orthop, April 2016; Vol-6 (1-2), P.42-47